Interactive teaching mode in college English on students’ social phobia - Li, Zhuo (CNS spectrums, 2023)
BackgroundSocial phobia is a common psychological disorder, particularly common among college students. College English, as a compulsory course, provides an opportunity for implementing an interactive teaching model. By implementing an interactive teaching model, students can more actively participate in classroom discussions, group activities, and role-playing, thereby enhancing their social skills and confidence.Subjects and MethodsThis study selected English teachers and 86 students from a university as the research subjects. By comparing the differences in students’ social fear levels between traditional and interactive teaching modes, the traditional teaching group usually adopts traditional face-to-face teaching methods for learning. The interactive teaching group adopts a more interactive and participatory teaching approach, using methods such as classroom discussions, group activities, experiments, and applications. This study used SPSS23.0 statistical software to analyze the data.ResultsIn the experiment, the scores of social phobia patients in the traditional teaching group showed a decreasing trend on the Self Rating Anxiety Scale, from 58.64 points to 34.16 points; The score of the interactive teaching changed from 60.24 points to 52.77 points. By comparing the scores of the interactive teaching group and the traditional teaching group, the interactive teaching mode of college English can improve communication skills of patients with social phobia.ConclusionsThe study adopted an interactive teaching model in college English teaching, and found that the symptoms of social phobia among college students were alleviated to some extent, which had a positive impact on their mental health.AcknowledgementChongqing Federation of Social Sciences (No. 2022WYZX32).